Interplay between intrachain and interchain interactions in semiconducting polymer assemblies: the HJ-aggregate model - Yamagata, H; Spano, F C (The Journal of chemical physics, 2012)
A new model for analyzing the photophysics of polymer aggregates is introduced taking into account exciton motion along a polymer chain and across polymer chains. Excitonic coupling and vibronic coupling are treated on equal footing using a Holstein-based Hamiltonian represented in a multi-particle basis set. In the HJ-aggregate model the competition between intrachain (through-bond) coupling leading to Wannier-Mott excitons, and interchain (through-space) coupling leading to Frenkel excitons, is studied in detail for two model dimers: one composed of red-phase polydiacetylene (PDA) chains and the other composed of regioregular P3HT chains. The resulting photophysical properties are shown to depend critically on the relative magnitudes of the intrachain and interchain exciton bandwidths. Dominant intraband (interband) coupling favors a photophysical response resembling J-aggregates (H-aggregates). In PDA dimers, where intrachain coupling prevails, the absorption spectrum is dominated by the 0-0 peak, as is characteristic of J-aggregates. The photoluminescence (PL) spectrum displays hybrid character: the ratio of the main (0-0) band to the first vibronic sideband intensities is initially zero at T = 0 K due to the forbidden nature of the 0-0 transition, but then increases with temperature in a manner characteristic of H-aggregates, peaking when kT ≈ ΔE, where ΔE is the interchain splitting. Further increases in temperature result in a decline of the PL ratio, as in a J-aggregate. This remarkable H to J transition is also predicted for the temperature dependence of the radiative decay rate, k(rad). The maximum (peak) rate scales as, k(rad) (max)∼(W(intra)/W(inter))(1/2), where W(intra) (W(inter)) is the intrachain (interchain) exciton bandwidth. Hence, when W(intra) is sufficiently larger than W(inter) the dimer displays thermally activated superradiance. In P3HT the intrachain coupling is far weaker than in PDA making the intrachain and interchain couplings comparable in the crystalline phase. Although the absorption spectral line shape is still well-accounted for by the conventional H-aggregate model, the photoluminescence is more sensitive, with H or J behavior tunable by changes in morphology. Long range intrachain order which coincides with weaker interchain interactions induces J-aggregate behavior, while short range intrachain order and the resulting stronger interchain coupling induces H-aggregate behavior. Our predictions neatly account for the H-like dominance exhibited by the PL from spin-cast films and the J-like dominance exhibited by the PL from highly ordered P3HT nanofibers self-assembled in toluene.